INNOVATIVE PROCESSES IN AIC: PROBLEMS AND PERMITS - A. Kamalova; R. Tagibova; M. Kardashova; A. Uzarhanova (Вестник университета)
The article deals with the concepts of innovation and innovation processes in agriculture, provides f classification of the types of innovations. It suggests ways to enhance innovation activity in the agriculture sector of the Russian Federation.